Particle Size and Heating Rate Effects on the Pyrolysis Kinetics of Aceh Low-Rank Coal : Kinetics, Thermal Decomposition, and Thermodynamic - Almardhiyah, Fadhilah; Mahidin; Khairil; Abnisa, Faisal (ASEAN Journal of Chemical Engineering, 2025)
This research aims to understand the combustion mechanism of Aceh’s low rank coal by studying the kinetics of the pyrolysis reaction using the thermogravimetric method. This study was carried out by testing coal samples at various pyrolysis temperatures between 0 and 600oC by varying the coal particle sizes of 5, 10, and 15 mesh, as well as different heating rates of 20, 40, and 60 K/minutes in a nitrogen atmosphere. The data TG-DTG obtained are used to divide into three stages and calculate the mass conversion rate and analyze key parameters such as reaction rate constant, exponential factor and activation energy (E, A, and n). Thus, the pyrolysis reaction rate mechanism can be formulated as a function of temperature and time. Mathematical modeling can be compared with the kissenger, coats-Redfern, DAEM model. The findings of this investigation indicate that coal pyrolysis adheres to the first-order kinetics mechanism, exhibiting an average activation energy of 37-75 kJ/mol and a pre-exponential factor of 0.091- 1.8 x 107 min–1. Thermodynamic parameters, the average enthalpy change (ΔH), entropy change (ΔS), and free energy change (ΔG) associated with coal pyrolysis, are computed to be 2.6-7.3 kJ/mol, –332 kJ/mol/s, and 89-431 kJ/mol, respectively. A pyrolysis, yielding an optimal oil output of 57.04 wt% at 320°C. This empirical investigation has the potential to enhance the combustion properties of low-rank coal, particularly with regard to ignition efficiency and maximum weight reduction, thereby suggesting the viability of utilizing low-rank coals in co-combustion applications as a fuel source